PENGARUH KEPADATAN BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN PATIN YANG DI PELIHARA DALAM WADAH HAPPA DI BBIS NOEKELE KABUPATEN KUPANG - Widia, Umar; Sunadji, Sunadji; Linggi, Yulianus (Nusa Cendana University, 2025)
This study aims to determine the effect of different stocking densities on the growth and survival of striped catfish (Pangasius sp.) fry reared in hapa net enclosures at the Central Fish Hatchery (BBIS) Noekele, Kupang Regency. The study employed a Completely Randomized Design (CRD) with three different stocking densities: 90, 120, and 150 fish per hapa, each replicated three times. The observed parameters included survival rate, absolute weight gain, absolute length gain, and water quality (temperature, pH, dissolved oxygen, and ammonia). Data were analyzed using ANOVA to assess the significance of differences among treatments, followed by the Least Significant Difference (LSD) test if significant differences were found. The results showed that different stocking densities had a significant effect on the survival and growth of catfish fry. ANOVA results indicated that stocking density had a significant effect (p < 0.05) on survival rate, but not on absolute weight gain or absolute length gain. The density of 90 fish per hapa yielded the best results, with higher survival rates, weight gain, and length gain compared to the densities of 120 and 150 fish per hapa. This condition suggests that at lower densities, competition for oxygen, space, and feed is reduced, thereby supporting more optimal growth. Therefore, a stocking density of 90 fish per hapa is recommended as an effective cultivation strategy to enhance the performance of catfish fry in the region. Keywords: Cultivation of hapa, catfish, density, growth, survival rate